2020
DOI: 10.1002/cld.866
|View full text |Cite
|
Sign up to set email alerts
|

Use of Statins in Patients With and Without Liver Disease

Abstract: http://aasldpubs.onlinelibrary.wiley.com/hub/journal/10.1002/(ISSN)2046-2484/video/15-1-reading-prashanth a video presentation of this article https://aasldpubs.onlinelibrary.wiley.com/hub/journal/20462484/video/15-1-interview-francis an interview with the author

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 40 publications
(64 reference statements)
0
16
0
Order By: Relevance
“… 27 , 28 Francis and Forman reported that clinically relevant risks to the liver from statins remain remarkably low in patients without cirrhosis and should not outweigh the broad cardiovascular and potential hepatic benefits. 29 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 27 , 28 Francis and Forman reported that clinically relevant risks to the liver from statins remain remarkably low in patients without cirrhosis and should not outweigh the broad cardiovascular and potential hepatic benefits. 29 …”
Section: Discussionmentioning
confidence: 99%
“…27,28 Francis and Forman reported that clinically relevant risks to the liver from statins remain remarkably low in patients without cirrhosis and should not outweigh the broad cardiovascular and potential hepatic benefits. 29 Due to the lack of evidence between statin use and severe liver injury, the National Lipid Association's Liver Expert Panel concluded that routine liver function monitoring might inappropriately encourage doctors to discontinue statin therapy upon detection of liver enzyme elevations. 30 Likewise, the FDA concurs that routine periodic monitoring of liver enzymes does not appear to be effective in detecting or preventing serious liver injury given the rarity and unpredictability of serious liver injury with statins in individual patients.…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with small prospective and larger retrospective studies that found statins to be safe in compensated cirrhosis. ( 39 ) Further studies are currently being performed assessing the safety and efficacy of different doses of statins in patients with decompensated cirrhosis. ( 40 ) In fact, we could not exactly determine the defined daily doses, and information on type or dose was not available in a subgroup of our patients.…”
Section: Discussionmentioning
confidence: 99%
“…(2) The underlying mechanisms for these benefits are not limited to low-density lipoprotein-lowering effects, but instead reflect a pleiotropic model in which complex changes in cellular signaling result in multimodal mechanisms of action that include anti-inflammatory, antifibrotic, and antioncogenic pathways. (1) In light of these pleiotropic effects, it is not surprising that benefits of statins have been found beyond cardiovascular event reduction. In addition to the aforementioned hepatoprotective effects, there is evidence suggesting a beneficial role of statins in the prevention of venous and arterial thrombosis.…”
Section: See Article On Page 1432mentioning
confidence: 99%